STUDI KASUS: KONSUMSI PUTIH TELUR UNTUK MEMPERCEPAT PENYEMBUHAN LUKA PERINEUM - Sri Yuliana; Siska Febrina Fauziah (Poltekkes Kemenkes Maluku, 2021)
Perineal suturing due to spontaneous obstetric tears or episiotomy is the most common operative procedure experienced by women. More than 90% of primiparas experience trauma to the labia, vagina or perineum during vaginal delivery. Perineal wound healing duration is influenced by nutritional factors. This case study describes the wound healing process in two primiparas who had second-degree perineal tears. Both of those primiparas have the same socio-economic characteristics. One primipara was given additional nutrition intake of 140 grams egg white per day, while the other primipara was given standard care of education related to perineal wound care and nutritional needs during puerperium. Perineal wound observation was performed using REEDA scale, while daily intake data were collected using a food recall form. Primipara who consumed egg white every day had an average protein intake of 89 grams and her perineal wound recovered in 6 days. Meanwhile, primipara who only received standard care had an average protein intake of 67 grams and her perineal wound recovered in 8 days. Perineal wound healing was faster in primipara who received additional protein intake from egg white consumption. So that, education related to nutritional needs during puerperium is important to inform the mother and family.